Associations between newly discovered polymorphisms in the Bos taurusgrowth hormone receptor gene and performance traits in Holstein-Friesian dairy cattle - Waters, S.M; McCabe, M.S; Howard, D.J; Giblin, L; Magee, D.A; MacHugh, D.E; Berry, D.P (Animal genetics, 2011)
Variations in the growth hormone receptor (GHR) gene sequence are associated with performance traits in cattle. For example, the single nucleotide polymorphism (SNP) F279Y in transmembrane exon 8 has a strong association with milk yield. In this study, 32 previously unreported, putative novel SNPs (31 in the 5′ non-coding region) were identified by resequencing ∼19 kb of the GHR gene in genomic DNA from 22 cattle of multiple breeds. A population of 848 Holstein-Friesian AI sires was subsequently genotyped for the 32 putative novel SNPs and seven published SNPs (including F279Y, one in exon 1A promoter and five in exon 10). Associations between each segregating SNP and genetic merit for performance were quantified in the 848 Holstein-Friesians using weighted animal linear mixed models. Six of the published SNPs and seven of the novel SNPs were associated with at least one of the traits - milk yield, fat yield, protein yield, fat percentage, protein percentage, somatic cell score, calving interval, survival and growth and size traits. Even when the allelic substitution effect (P < 0.001) of F279Y was accounted for, the allelic substitution effect of one of the novel SNPs (GHR4.2) in the 5′ non-coding region of GHR was associated with a lactation milk yield of 37.46 kg (P < 0.001). GHR4.2 and F279Y were not in linkage disequilibrium (r² = 0.00, D' = 0.04) in the 848 Holstein-Friesians, indicating that their association with milk yield was independent.